Unhelpful Thoughts and Distress Regarding Symptoms Limit Accommodation of Musculoskeletal Pain. Issue 2 (15th February 2022) - Teunis, Teun; Al Salman, Aresh; Koenig, Karl; Ring, David; Fatehi, Amirreza
Abstract: Background: Among people with musculoskeletal disorders, much of the variation in magnitude of incapability and pain intensity is accounted for by mental and social health opportunities rather than severity of pathology. Current questionnaires seem to combine distinct aspects of mental health such as unhelpful thoughts and distress regarding symptoms, and they can be long and burdensome. To identify personalized health strategies, it would be helpful to measure unhelpful thoughts and distress regarding symptoms at the point of care with just a few questions in a way that feels relevant to a person's health. Questions/purposes: (1) Do questions that address unhelpful thoughts and distress regarding symptoms independently account for variation in accommodation of pain? (2) Which questions best measure unhelpful thoughts and distress regarding symptoms? Methods: This is a cross-sectional questionnaire study of people seeking care regarding upper and lower extremity conditions from one of eight specialist clinicians (one upper extremity, one arthroplasty, and one sports surgeon and their three nurse practitioners and two physician assistants) in one urban office. Between June 2020 and September 2020, 171 new and returning patients were approached and agreed to participate, and 89% (153) of patients completed all questionnaires. The most common reason for noncompletion was the use of a pandemic strategy allowing people to use their phone to finish the questionnaire, with more people leaving before completion. Women and divorced, separated, or widowed people were more likely to not complete the survey, and we specifically account for sex and marital status as potential confounders in our multivariable analysis. Forty-eight percent (73 of 153) of participants were women, with a mean age 48 ± 16 years. Participants completed demographics and the validated questionnaires: Pain Catastrophizing Scale, Negative Pain Thoughts Questionnaire, Tampa Scale of Kinesiophobia, Intolerance of Uncertainty Scale, and Pain Self-Efficacy Questionnaire (a measure of accommodation to pain). In an exploratory factor analysis, we found that questions group together on four topics: (1) distress about symptoms (unhelpful feelings of worry and despair), (2) unhelpful thoughts about symptoms (such as worst-case thinking and pain indicating harm), (3) being able to plan, and (4) discomfort with uncertainty. We used a multivariable analysis, accounting for potential confounding demographics, to determine whether the identified question groupings account for variation in accommodation of pain—and thus are clinically relevant. Then, we used a confirmatory factor analysis to determine which questions best represent clinically relevant groupings of questions. Results: After accounting for sex, marital status, work, and income, we found that distress and unhelpful thoughts about symptoms were independently associated with accommodation of pain, and together, they explained 60% of its variation (compared with 52% for distress alone and 40% for unhelpful thoughts alone). Variation in symptoms of distress was best measured by the question "I feel I can't stand it anymore" (76%). Variation in unhelpful thoughts was best addressed by the question "I wouldn't have this much pain if there wasn't something potentially dangerous going on in my body" (64%). Conclusion: We found that distress (unhelpful feelings) and unhelpful thoughts about symptoms are separate factors with important and comparable associations with accommodation to pain. It also appears that these two factors can be measured with just a few questions. Being attentive to the language people use and the language of influential questions might improve clinician identification of mental health opportunities in the form of distress and unhelpful thoughts about symptoms, which in turn might contribute to better accommodation and alleviation of symptoms. Level of Evidence: Level II, prognostic study.